Is behavioral economics doomed? the ordinary versus the extraordinary - Levine, David K.; Max Weber Programme; Open Book Publishers (Open Book Publishers, 2012)
"It is fashionable to criticize economic theory for focusing too much on rationality and ignoring the imperfect and emotional way in which real economic decisions are reached. All of us facing the global economic crisis wonder just how rational economic men and women can be. Behavioral economics - an effort to incorporate psychological ideas into economics - has become all the rage.This book by well-known economist David K. Levine questions the idea that behavioral economics is the answer to economic problems. It explores the successes and failures of contemporary economics both inside and outside the laboratory. It then asks whether popular behavioral theories of psychological biases are solutions to the failures. It not only provides an overview of popular behavioral theories and their history, but also gives the reader the tools for scrutinizing them. Levine's book is essential reading for students and teachers of economic theory and anyone interested in the psychology of economics."--Publisher's website.
1. Introduction -- 2. Does economic theory work? -- 3. Why is the world so irrational? -- 4. Does economic theory fail? -- 5. You can fool some of the people ... -- 6. Behavioral theories I : biases and irrationality -- 7. Behavioral theories II : time and uncertainty -- 8. Learning and friends -- 9. Conclusion: Psychology, neuroscience and economics.
Available through Open Book Publishers.
Includes bibliographical references (pages 131-138) and index.
Mode of access: World Wide Web.
Keywords: Consumers' preferences; Economics -- Psychological aspects; Rational choice theory